Ernesto Quesada: una trayectoria en transición. La escritura de la historia familiar y la construcción de la historiografía en Argentina - Barbato, Dante (Historiografías, 2021)
In this article we shall examine some historiographic activities made by Ernesto Quesada (1858-1934) that show us his trajectory understood as a transition between the writing of family history and the production on a new image of Juan Manuel de Rosas’ governments. This intellectual challenge was based on a set of rules and renewal methods that helped shape the difficult process of construction of the historiographic field in Argentina. We shall focus on the use of some documentary sources by Quesada, the way of accessing to private files at that time of fragile institutionalization of historical studies, and his joining to the discussion on the national past. Keywords Ernesto Quesada, Argentine historiography, family history, methodological renewal, files, Juan Manuel de Rosas.